Persistent Extreme Hyperextension of the Fetal Neck: Clinical and Neuroimaging Findings. Issue 3 (5th February 2018) - Shrot, Shai; Johnson, Clark T.; Golden, W. Christopher; Baschat, Ahmet A.; Bullard, Janine E.; Tekes, Aylin; Poretti, Andrea; Dunn, Emily; Huisman, Thierry A.G.M.
ABSTRACT: BACKGROUND AND PURPOSE: Persistent hyperextension of the fetal craniocervical junction or neck is one of several fetal positions commonly observed on prenatal imaging. Underlying fetal structural etiologies such as fetal neck masses and iniencephaly can be detected as causes of hyperextension. Caesarean delivery is considered in cases of vaginal delivery or obstructed labor for fear of cervical spinal cord injury. In this case series, we describe the prenatal magnetic resonance imaging (MRI) findings and their potential role in obstetric management and discuss postnatal outcomes in fetuses demonstrating prenatal imaging findings of persistent extreme hyperextension of the neck. METHODS: A retrospective cohort of fetuses with extreme fetal neck hyperextension on prenatal ultrasound and subsequent MRI is described. RESULTS: Persistent extreme neck hyperextension was demonstrated in four pregnancies. One patient showed resolution of head positioning prior to labor. In the other 3 patients, neck hyperextension persisted until labor. In these three pregnancies, caesarean section with early intubation was performed due to concern for airway compromise and cervical cord injury. An underlying structural neck abnormality with airway compromise was noted only in 1 patient (large venolymphatic malformation). No airway compromise, cervical spine, or spinal cord anomaly was identified in the remaining 3 patients. Noncervical fetal anomalies were detected only in 1 patient (arthogryposis multiplex and clubfoot deformities). In patients with no structural neck abnormality, early extubation was performed shortly following labor. CONCLUSIONS: Detailed, high‐resolution fetal MRI may serve as a valuable secondary imaging modality for clinical decision making regarding management of pregnancy, in utero therapy, mode of delivery, and postnatal care.